Exploring the effect of fibers on texture, fire performance and sprayability of intumescent coating - Hui, Man Yuen (Nanyang Technological University, 2024)
Structural steel is a common material used in the building and construction industry and the marine industry due to its strength, durability, recyclability, ease of fabrication and its cost effectiveness. However, one major disadvantage of steel is that it loses strength and becomes ductile at 500°C. In a case where there is a fire breakout, temperatures can hit up to 815°C, losing its strength significantly. As a result, fire protection is crucial for providing time to evacuate. Intumescent coating provides a protective shield by forming a char layer but even so, the char layer lacks structural integrity and may not protect steel from fire effectively. Therefore, fibre reinforcement is required to provide the char strength. This project investigates how different fiber material and aspect ratio will affect the spraying process in terms of maximum wet thickness per spray due to fiber entanglement and viscosity of the coating and the char expansion and rigidity of the residue char. Coatings are sprayed on to a (100x100x10) mm steel substrate with thickness of 3.5mm for furnace test and maximum wet thickness for each formulation were also tested with different fiber materials, fiber length and weight percentage. 3 dissimilar materials are investigated: Carbon fiber, glass fiber and basalt fiber with fiber length from 0.15mm to 3mm. Maximum wet thickness is also investigated using the maximum fiber concentration for each type of fiber. It was observed that fiber length and concentration determine the viscosity as well as the maximum wet thickness per spray pass. All fire performance test is conducted under the ISO 834 fire curve simulation. Results have shown that CF 1mm with 3.51% weight content has the best fire performance in terms of the longest time taken to delay heat transfer from furnace to the back plates of structural steel. Analysis of the char residue suggest that char expansion and rigidity is a principal factor to determine its fire-retardant properties.